“UNDANG-UNDANG BAHASA”: SEBUAH INSTRUMEN BAGI PEMBINAAN BAHASA DALAM ERA GLOBALISASI*) - E Zaenal Arifin (Universitas Nasional, 2017)
Article and section on the language and literature in the Indonesia Language Act 24 of 2009 has a very hopeful nuance in the development of this era of information technology. However, the implementation of Language Development in the Globalization Era faces a very serious challenge. In fact, certain articles and sections are violated by a president who actually signed his own act. The Language Agency invites all stakeholders in the regions to make legal arrangements in the form of district regulation, mayor regulation, and governor regulation on language control in the public sphere. Indonesian can become an international language if started from the people of Indonesia itself. Indonesian leaders should love their language more than foreign languages, and play the role of international language at home and abroad through the United Nations.